Novel multi-stage aluminium production: part 2 – experimental investigation on carbosulphidation of Al2O3 using H2S and sodiothermic reduction of Al2S3. (2nd October 2017) - Huda, N.; Khaliq, A.; Rhamdhani, M. A.; Sheppard, D.; Brooks, G.; Monaghan, B.; Prentice, L.
ABSTRACT: In this paper, experimental investigation on the carbosulphidation of alumina (Al2 O3 ) for aluminium (Al) production and the sodiothermic reduction of aluminium sulphide (Al2 S3 ) are presented. Hydrogen sulphide (H2 S) was used as a reductant and source of sulphur. This work is the second of two-parts paper series. The experimental investigations of the Stage-1 process (Al2 O3 carbosulphidation) were carried out at 1100–1600°C using a laboratory scale horizontal tube resistance-furnace. H2 S gas, diluted with argon (5% H2 S and 95% Ar), was reacted with pellets of a mixture of γ-Al2 O3 and C powders (1:6 molar ratio) to produce Al2 S3 . The effects of gas injection rate, pelletizing pressure, temperature and reaction time on the conversion of Al2 O3 to Al2 S3 were investigated. The X-ray diffraction results confirmed the formation of Al2 S3 (s) in the reaction product above 1400°C. The conversion of Al2 O3 to Al2S3 was found to be 99.5% at 1600°C and 12 h. The kinetics analysis of alumina sulphidation using Ginstling-Brounshtein diffusion model suggested the overall reaction was controlled by the diffusion of H2 S gas through the reaction product (liquid Al2 S3 ). The activation energy of the alumina sulphidation reaction was calculated to be 148.5 kJ mol −1 . It has also been demonstrated in this study that Al can be extracted from Al2 S3 by sodiothermic reduction using Na or NaH. In the case of Na, a level of Al conversion of 75% has been observed for reaction at 290°C.